ROLE OF IRRADIATION AND STATUS OF Α-FETO PROTEIN, Β2- MICROGLOBULIN AND CARCINOEMBRYONIC ANTIGEN IN DIFFERENT STAGES OF ORAL CANCER PATIENTS - CHITRA S (International Journal of Pharma and Bio Sciences, 2015)
Head and neck cancers are a major cancer burden in India. Men are at high risk for oral cancer, especially smokers and alcohol drinkers are more susceptible. Areca nut, often used with betel quid and chewable tobacco is the fourth most commonly used psycho-active substance in the world, ranking after caffeine, alcohol and nicotine. They share a common risk factor profile, including regular consumption of products of betel, areca and tobacco. Analysis of tumor markers in oral cancer is important to understand the severity of the disease. In this work, across-sectional study was carried out to understand the relation of socio-demographic factors with tobacco toxicity in part of Indian population. Sociodemographic variables of patients were noted on through various questionnaires of standard format. Serum α-feto protein (AFP), β2-microglobulin (β2m) and carcinoembryonic antigen (CEA) were analyzed before and after treatment with radiotherapy in oral cancer patients. The frequency of this cancer was found to be higher in the age of 45-60 years; People who chewed tobacco, spicy food with animal fat, poor oral hygiene, and low educational status were shown to have oral cancer. Lack of awareness of the risk factors for oral cancer leads to delay in diagnosis of the disease poor survival of the patients. With these considerations, the present study designed to determine the socio-demographic factors which are involved in oral cancer development by habitual use of the above products. Alterations in the levels of cancer markers in oral cancer patients were observed in different stages of oral cancer. The treatment efficacy shows the regression of the tumor in oral cancer patients. Systematic, high-quality and theory-driven research in this area is immediately needed to improve the healthcare of the patients.